News Pandemi Covid-19 in Mass Media Online Fajar.co.id (Critical Discourse Analysis) - Muhlisa Muhlisa; Ramly Ramly; Usman Usman (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to: Analyze the semantic, syntactic, stylistic, and rhetorical elements of the covid-19 pandemic news text on the online mass media Fajar.co.id. This type of research is descriptive qualitative, the basis of the research using the critical discourse analysis method of Teun a Van Dijk. This research was conducted on the online mass media Fajar.co.id. It is one of the online mass media portals originating from the city of Makassar which is well known and considered to have actual and accurate news, this is proven by the number of public access that has reached tens of thousands of readers within 3 days. As of March-April 2021, researchers have received 30 news texts to be studied. This research will be carried out from May to June 2021 and carried out on the online mass media Fajar.co.id. The data collection technique used in this research is critical reading and citing things that are needed as complementary data. The steps of data collection techniques are, text observation, through direct observation or observation on the text to be studied. Identify and analyze covid-19 news texts in the online mass media Fajar.co.id. Marking important things related to the micro structure of the covid-19 news text in the online mass media Fajar.co.id. Transferring important data related to the microstructure of the covid-19 news text that is available on the online mass media of Fajar.co.id. Categorize the microstructure data of the covid-19 news text in the online mass media Fajar.co.id.Keywords: Pandemic, Covid-19, News Text, Critical Discourse Analysis